2014
DOI: 10.1002/eji.201444490
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin‐induced expression of CXCL10 mediates direct fungal killing and recruitment of NK cells to the cornea in response to Candida albicans infection

Abstract: We previously showed that topical flagellin induces profound mucosal innate protection in the cornea against microbial infection, a response involving multiple genes and cell types. In this study, we used a Candida albicans (CA)-C57BL/6 mouse keratitis model to delineate the contribution of CXCL10 and CXCR3-expressing cells in flagellin-induced protection. Flagellin-pretreatment markedly enhanced CXCL10 expression at 6 hours post CA infection (hpi), but significantly dampened CXCL10 expression at 24 hpi. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 52 publications
2
30
1
Order By: Relevance
“…This is different from flagellin-treated corneas, where CXCR3-positive cells were found in the stroma beneath the epithelium (29). At 1 dpi, as shown above, CXCL10 was mostly expressed in the damaged epithelium, while CXCR3 was found in the infiltrating cells in the stroma or in an intraepithelial cell cluster that contained mainly natural killer cells and neutrophils (29). Interestingly, exogenous CHI3L1 markedly increased epithelial expression of CXCL10 and the number of CXCR3-positive cells in the stroma.…”
Section: Figcontrasting
confidence: 73%
See 3 more Smart Citations
“…This is different from flagellin-treated corneas, where CXCR3-positive cells were found in the stroma beneath the epithelium (29). At 1 dpi, as shown above, CXCL10 was mostly expressed in the damaged epithelium, while CXCR3 was found in the infiltrating cells in the stroma or in an intraepithelial cell cluster that contained mainly natural killer cells and neutrophils (29). Interestingly, exogenous CHI3L1 markedly increased epithelial expression of CXCL10 and the number of CXCR3-positive cells in the stroma.…”
Section: Figcontrasting
confidence: 73%
“…CHI3L1 alone induced CXCL10 and CXCR3 expression at 4 h, mostly in the basal layers of the epithelium. This is different from flagellin-treated corneas, where CXCR3-positive cells were found in the stroma beneath the epithelium (29). At 1 dpi, as shown above, CXCL10 was mostly expressed in the damaged epithelium, while CXCR3 was found in the infiltrating cells in the stroma or in an intraepithelial cell cluster that contained mainly natural killer cells and neutrophils (29).…”
Section: Figmentioning
confidence: 79%
See 2 more Smart Citations
“…A recent study demonstrated that flagellin up-regulated CXCL10 expression in the cornea and that this contributed to fungal clearance through a CXCR3-dependent NK cell response (43). CXCL9, CXCL10, and CXCL11 are members of the IFN-inducible CXC chemokine family that act through interaction with the CXCR3 (44,45) receptor found on a variety of cell types, including NK cells (45,46).…”
mentioning
confidence: 99%